Perlindungan Hukum Bagi Debitur Pailit Untuk Mewujudkan Asas Kelangsungan Usaha Pada Masa Covid-19 - Reniwurwarin, Alfin Mubin; Saija, Ronald; Labetubun, Muchtar Anshary Hamid (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The Covid-19 pandemic has had so many impacts on social life, especially in the economic field, many debtors are experiencing difficulties in paying their debts because of Covid-19, Law Number 37 of 2004 concerning bankruptcy and suspension of debt payment obligations as a settlement of bankruptcy disputes becomes alternative in the debtor's efforts so that the debtor gets out of bankruptcy and can resume his business.Purposes of the Research: The purpose of this paper is to find out the factors that led to debtors going bankrupt during the Covid-19 period and efforts to protect debtors who are experiencing bankruptcy so they can continue their business again.Methods of the Research: The type of research used in this paper is normative legal research. As for answering the problems in this study, the authors use three approaches to the problem, namely the statutory approach (statute approach), and conceptual approach (conceptual approach). The procedure for collecting legal materials carried out by the author is by searching for and collecting laws and regulations related to the legal issues at hand. Legislation in this case includes both legislation and regulation. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained legislation and legal norms that exist in society.Results of the Research: The results of this study indicate that the factors that influence bankrupt debtors during the Covid-19 period, namely, General Factors and External and Internal Factors, in an effort to protect debtors from continuing their business are preventive and repressive with the orientation of applying Force Majuere, debt restructuring and providing justice for bankrupt debitor.